Effect of Noradrenaline on the Virulence Properties of Campylobacter Species - Sree V. Aroori; Tristan A. Cogan; Tom J. Humphrey (International Journal of Microbiology)
Campylobacter species cause a spectrum of illnesses in humans. The type of illness and the outcome is dependent on the virulence of the infecting pathogen strain and host immune status. Acute stress can seriously compromise host immunity and increase susceptibility to infection. Noradrenaline (NA) is a stress hormone. Several studies have shown that it stimulated growth and increased the pathogenicity of organisms including E. coli and Campylobacter jejuni. However, the effect of NA on other Campylobacter species is unknown. We have examined the effect of NA on growth rate, motility, invasion of T84 epithelial cells, and colonisation of chickens by diverse Campylobacter species. Campylobacter cultures grown with NA had reduced lag phases, increased growth rates, and higher final optical densities than controls. The motility of Campylobacter was also significantly increased in the presence of noradrenaline. Some of the Campylobacter strains tested also showed increased invasion of T84 epithelial cells, greater breakdown of tight junctions, and an enhanced potential to colonise chickens. Our results show that noradrenaline-induced enhancement of virulence of Campylobacter can influence the outcome of infection.